Intracellular polarization of RNAs and proteins in the human small intestinal epithelium. - Roy Novoselsky; Yotam Harnik; Oran Yakubovsky; Corine Katina; Yishai Levin; Keren Bahar Halpern; Niv Pencovich; Ido Nachmany; Shalev Itzkovitz (PLoS Biology)
The intestinal epithelium is a polarized monolayer of cells, with an apical side facing the lumen and a basal side facing the blood stream. In mice, both proteins and mRNAs have been shown to exhibit global basal-apical polarization; however, polarization in the human intestine has not been systematically explored. Here, we employed laser-capture microdissection to isolate apical and basal epithelial segments from intestinal tissues of 8 individuals and performed RNA sequencing and mass-spectrometry proteomics. We find a substantial polarization of mRNA molecules that largely overlaps polarization patterns observed in mice. This mRNA polarization remains consistent across different zones of the intestinal villi and is generally correlated with the polarization of proteins. Our protein analysis exposes streamlined intracellular nutrient transport and processing and reveals that mitochondria and ribosomes are less polarized in humans compared to mice. Our study provides a resource for understanding human intestinal epithelial biology.